The Neoliberal Chilean Process Four Decades after the Coup - Valdés, Pablo Cuevas (Social justice, 2013)
The authors provides an overview of the Neoliberal Chilean Process forty years after the Chilean military dictatorship of Augusto Pinochet Ugarte. Topics discussed include pattern of reproducing capital in Chile, procedural democracy in Chile, and the associated sociocultural mechanisms. Other topics discussed include inefficiency of the import-substitution industrialization (ISI) development model and underdevelopment in the Chilean agricultural sector.